The effect of repeated bouts of downhill training on running performance and recovery after a 30-km time trial - Schutte, Lynne (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Purpose: The present study was designed to examine the effect of repeated bouts of either downhill or level running on running performance in, and recovery from, a 30-km time trial. Methods: Sixteen male subjects with a mean (± SD) age of 33.8 ± 5.8 years, body mass of 72.0 ± 7.3 kg and a stature of 176.6 ± 4.5 cm were randomly allocated to either a downhill (n=9) or a level group (n=7). The protocol consisted of a training phase, followed by a 30-km time trial and a recovery phase. During the training phase subjects ran either at a -10% grade (downhill group) or a 0% grade (level group) on a treadmill for nine 40-minute training runs [70% of peak treadmill running speed (PTRS)]. Thereafter all the subjects participated in a 30-km time trial (70% of PTRS), where heart rate (HR), rate of perceived exertion (RPE) and stride length (SL) were recorded, followed by five 15-minute submaximal recovery runs. The first recovery run was performed before the start of the training phase and again on four occasions after the 30-km time trial. HR, RPE, SL, minute ventilation (Vi), oxygen consumption (VO₂), carbon dioxide production (VCO₂) and respiratory exchange ratio (RER) were recorded during these 15-minute runs. Plasma creatine kinase (CK) activity and muscular soreness were assessed for the duration of the study. Results: HR decreased in the downhill group during the training phase, suggesting a HR training effect. Muscle pain and plasma CK activity in the downhill group increased after the first 40-minute downhill training run. These indicators of muscle damage did not show any further increases during the training phase, suggesting a "repeated bout effect". Towards the end of the 30-km time trial the level group, showed a greater heart rate drift (HRD) and an increased RPE, suggesting that they were not able to resist fatigue to the same extent as the downhill group. HR and RPE recorded during the recovery phase suggested that the downhill group showed a better recovery after the 30-km time trial. During the recovery phase the downhill group experienced no increase in muscle pain after performing the 30-km time trial, in contrast to the level group who experienced muscle pain for five days after the 30-km time trial. Plasma CK activity, was blunted after the 30-km time trial in the downhill group in contrast to the level group. Conclusion: The results of the investigation support the hypothesis that the inclusion of downhill training into a training program cause changes, which can be interpreted as enhancing performance during an endurance event and recovery after the event.